Colonial churches of Huaura and Checras’ river - González Castrejón, Sara (2018)
This article introduces the colonial temples of Huaura and Checra’s river valleys in the sierra of Lima; a surprising example of Peruvian vernacular architecture with baroque and neo-classical altarpieces, mural paintings and historical furnishing which sit in spectacular natural surroundings. We aim to disseminate their interesting history and show their potential as a tourist attraction in connection with the natural and cultural resources of the area, such as lagoons, peaks, thermal waters, archaeological remains, popular festivals, folklore and local gastronomy. For that we will study these churches from the artistic point of view and suggest some routes which could be easily implemented.